Nutritional Content of Fermented Kepok Banana Peel (KBP) by Local Microorganisms (MOL) - Munthe, V.P.G.P.; Wahyuni, T.H.; Yunilas; Siregar, Y. (Talenta Publisher, 2021)
KBP is a waste from processing of Kepok banana which has not been used optimally because it has low nutritional content. One way to improve nutritional quality of KBP by fermentated process. This study aims to examine the nutritional content of fermented KBP with various doses of MOL and fermentation time. The research was conducted by using an experimental method using a completely randomized design (CRD) with 3 x 3 factorial pattern and 3 replications. The first factor was various doses (D1 = 1%; D2 = 3%; D3 = 5%) and second factor was fermentation time (L1 = 3 days; L2 = 5 days; L3 = 7 days). The variables observed were moisture and dry matter content, crude protein, crude fat, crude fiber, ash, and BETN. The results showed that fermentation of KBP using various doses of MOL had a very significant effect (P <0.01) on moisture content, dry matter, crude protein, ash, but had no significant effect (P> 0.05) on crude fiber, crude fat and BETN. Fermentation time had no significant effect (P> 0.05) on moisture content, dry matter, crude protein, crude fiber, crude fat, and BETN, but had a very significant effect (P <0.01) on ash content. There was an interaction between MOL dose and fermentation time on BETN levels but there was no interaction between MOL dose and fermentation time on moisture content, dry matter, crude protein, crude fiber, crude fat and ash. The conclusion of this research is fermentation of KBP using MOL up to 5% increased dry matter content, crude protein, and decreased moisture content and ash content.